A SEMIOTIC STUDY OF ICON AND SYMBOL OF SUBARU CAR IN AUTOMOTIVE ADVERTISEMENT - Ariwibowo, Syamsuri; Priyaditya, Deka NP (Faculty of Letters, Dr. Soetomo University, 2016)
Advertisement is a media communication which mostly contains sign. In order to achieve the selling goals, companies will provide advertisement to introduce their product. In this matter, the thesis writer will be focused on analyzing sign in advertisement. One of the companies that is known world-wide for its car products and campaigns is Subaru, a Japanese brand of multifaceted transport equipment. There are two objectives intended to be solved in this thesis, they are to find the meaning and to find the role of icon and symbol in the ads picture of Subaru car in automotive magazine. The thesis writer applies qualitative research as her research design to analyze the sign in the ads. It is intended to the thesis writer to be able to gather information about meaning from social perspective. The study of this thesis will started by finding the meaning of icon and symbol by using triadic process, which is a semiosis theory by Charles Sanders Peirce. Finding out the symbol and icon meaning through represantamen and interpretant in triangle figure. After finding out the meaning behind the icon and symbol, the thesis writer will be able to describe the role of icon and symbol in Subaru car ads pictures. It is concluded that even from one company, the icon and symbol used somehow serves different vibes to each product. But characteristics of the company brand are not left behind. The meaning behind icon and symbol mostly shows that the Subaru car is suitable for every weather, tracks, well-known for its safety and has sustainable machinery. The role of icon and symbol in the ads itself combined to support the quality of the product.Â Â Key Words: Icon, Symbol, Representamen.